A Toxic System: Lord Douglas of Barloch and the Fight for ‘Natural’ Food and Water (1940s-60s) - Arnaud Page (Revue Française de Civilisation Britannique)
This article presents the ideas of a post-war Labour peer, Lord Douglas of Barloch (1889-1980), and his campaign against the industrial food system. While histories of environmentalism in Great Britain have mostly focused on responses to pollution and the preservation of landscapes, this article argues that food was a very powerful driver of environmental consciousness. The study of Douglas’ work, whose contribution to the organic movement has rarely been noticed by historians, shows that concerns about the potential toxicity of particular food items and processes were systematically related to broader questions about the impact of the British food system on health and the environment. The article thus shows how the House of Lords provided a forum for numerous discussions of food-related environmental issues in the post-war period, and also how the concerns expressed there were ultimately rarely taken into account by policy-makers.